Sources of Sport Confidence of Student Athletes with Disabilities - Sampan, Faith M.; Gomez, Marie Grace A. (Philippine Journal of Education Studies (formerly the Education Quarterly); Vol 73 No 1 (2015), 2015)
This study investigated the sources of sport confidence among Filipino student athletes with disabilities enrolled in different schools under an inclusionary setting. It also sought to find out if such sources of confidence vary with the type of disability the athletes have and the type of sport they play. The study was conducted among 63 athletes with visual, hearing, or orthopedic impairment. The participants came from different public schools in Quezon City and the Philippine Sports Association for the Differently Abled-National Paralympic Committee of the Philippines (PhilSPADA-NPC Philippines). To gather data, they were given the Athlete Self-rating Scale. Interviews were also conducted among them. Non-parametric statistics were used to synthesize and analyze data gathered. Results show that the top sources of sport confidence of student athletes with disabilities are environmental comfort, coach’s leadership, and social support. Results show that the top sources of sport confidence of student athletes with disabilities are environmental comfort, coach’s leadership, and social support. Further, sources of sport confidence differ with the disability the athletes have. Also, there is a difference in the sources of sport confidence based on the type of sport the athletes play. Keywords: sport confidence, athletes with disabilities